Cognitivety in museology-case Samarkand museums (Texas Journal of Philology, Culture and History, 2024)
In thesis, mainly aims to understand what cognitivity is and to study its relations with museums. Furthermore, it represents the concept of cognition and museum pedagogy which is teaching about the richness of the museum objects and their stories how use in the human mind. The task is to mediate between museum objects and visitors, ensure tactile, visual, auditory transmission of information. Every kind of activity are offered as well as to other visitor groups in the museum study. However, you will find answers to questions such as how the concept of cognition is applied in relation to the places and arguments. In addition to thesis, how we develop cognition in children and adults and there by attract them to museum. Because of the fact that interests of kids and teenagers especially are developing by releasing cognitive or on the contrary what causes cognitive decline. Cognativity connects with rest restoration, cultural heritage, robotics, information system, museography, time allocation, conservation, artificial vision,3DModelling, argumented reality